2016
DOI: 10.1038/ncomms11103
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic link between renal birth defects and congenital heart disease

Abstract: Structural birth defects in the kidney and urinary tract are observed in 0.5% of live births and are a major cause of end-stage renal disease, but their genetic aetiology is not well understood. Here we analyse 135 lines of mice identified in large-scale mouse mutagenesis screen and show that 29% of mutations causing congenital heart disease (CHD) also cause renal anomalies. The renal anomalies included duplex and multiplex kidneys, renal agenesis, hydronephrosis and cystic kidney disease. To assess the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 43 publications
3
61
0
Order By: Relevance
“…A small retrospective series reported that 30% of patients with CHD also had renal anomalies. 42 Although the true prevalence is likely lower, many pediatric cardiac centers actively screen patients with complex CHD for structural renal abnormalities. Renal artery stenosis is prevalent in nonsyndromic (familial supravalvular aortic stenosis) and syndromic (Williams-Beuren syndrome) elastin insufficiency and may contribute to the development of hypertension in those individuals.…”
Section: Overviewmentioning
confidence: 99%
“…A small retrospective series reported that 30% of patients with CHD also had renal anomalies. 42 Although the true prevalence is likely lower, many pediatric cardiac centers actively screen patients with complex CHD for structural renal abnormalities. Renal artery stenosis is prevalent in nonsyndromic (familial supravalvular aortic stenosis) and syndromic (Williams-Beuren syndrome) elastin insufficiency and may contribute to the development of hypertension in those individuals.…”
Section: Overviewmentioning
confidence: 99%
“…43 Also, at least 1 Robo1 mice mutant develops multiplex kidneys. 44 Furthermore, in situ hybridization analysis revealed Robo1 to be expressed in mice 14.5 dpc in a variety of tissues, including brain, spinal cord, eye, alimentary system, skeletal muscles, and limbs (www.eurexpress.org).…”
Section: Variant In Ret (+164761)mentioning
confidence: 99%
“…EC scan function assessment showed hyper functioning in four. These were giant palpable kidney in (1), solitary kidney (1) and contralateral dysplastic kidney in (2) UTI was initial presentation in (6), three had turbid urine on table, which grew organism on culture suggestive of pyonephrosis (2). Six infants developed postoperative UTI, three of whom were stented and responded to early stent removal.…”
Section: Resultsmentioning
confidence: 99%